Familial Periodic Fever, Aphthous Stomatitis, Pharyngitis and Adenitis Syndrome; Is It a Separate Disease? - Veres, Tamar; Amarilyo, Gil; Abu Ahmad, Sabreen; Abu Rumi, Maryam; Brik, Riva; Hezkelo, Nofar; Ohana, Orly; Levinsky, Yoel; Chodick, Gabriel; Butbul Aviel, Yonatan (Frontiers in Pediatrics, 2022)
Introduction: Periodic Fever, Aphthous Stomatitis, Pharyngitis, Adenitis (PFAPA) is the most common periodic fever syndrome in the pediatric population, yet its pathogenesis is unknown. PFAPA was believed to be sporadic but family clustering has been widely observed. Objective: To identify demographic and clinical differences between patients with PFAPA and a positive family history (FH+) as compared to those with no family history (FH-). Methods: In a database comprising demographic and clinical data of 273 pediatric PFAPA patients treated at two tertiary centers in Israel, 31 (14.3%) had FH+. Data from patients with FH+ were compared to data from those with FH-. Furthermore, family members (FMs) of those with FH+ were contacted via telephone for more demographic and clinical details. Results: The FH+ group as compared to the FH- group had more myalgia (56% vs. 19%, respectively, p= 0.001), headaches (32% vs. 2%, respectively, p= 0.016), and a higher carrier frequency of M694V mutation (54% vs. 25%, respectively, p=0.05). Colchicine was seen to be a more beneficial treatment for the FH+ group as compared to the FH- group; however, with no statistical significance (p=0.096). FMs displayed almost identical characteristics to patients in the FH+ group except for greater arthralgia during flares (64% vs. 23%, respectively, p=0.008), and compared to the FH- group they had more oral aphthae (68% vs. 43%, respectively, p=0.002), myalgia/arthralgia (64% vs. 19%/16%, respectively, p<0.0001), and higher rates of FH of Familial Mediterranean fever (FMF) (45% vs.15%, respectively, p=0.003). Conclusions: Our findings suggest that patients with a FH+ likely experience a different subset of disease with higher frequency of family history of FMF, arthralgia, myalgia, and better response to colchicine compared to FH-. Colchicine prophylaxis for PFAPA should be considered in FH+.